1991
DOI: 10.1172/jci115339
|View full text |Cite
|
Sign up to set email alerts
|

Lipolysis exposes unreactive endogenous apolipoprotein E-3 in human and rat plasma very low density lipoprotein.

Abstract: Endogenous apolipoprotein E in VLDL is poorly expressed in receptor binding processes The ligand responsible for receptor interaction of lipolyzed VLDL (apo E or apo B-100) and its source (endogenous or transferred) was studied with monoclonal antibodies and with lipoproteins from E-3/3 and E-2/2 subjects. The data unequivocally proved that lipolysis causes exposure of unreactive endogenous apo E-3 at the VLDL surface, possibly by a change of conformation of the protein. Apo B-100 becomes biologically expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 32 publications
3
47
1
Order By: Relevance
“…The difference between the uptake of control and transgenic VLDL was enhanced by pretreating the cells with lovastatin, suggesting an LDL receptor-mediated process. Previously it has been shown that rat (37,38) and human hypertriglyceridemic (39,40) VLDL uptake can occur through recognition of apo E on the VLDL by LDL receptors. This process was greatly increased by pretreating the VLDL with LPL (37) and it was suggested that the lipase allowed a conformational change in apo E to take place which in turn allowed receptor recognition.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the uptake of control and transgenic VLDL was enhanced by pretreating the cells with lovastatin, suggesting an LDL receptor-mediated process. Previously it has been shown that rat (37,38) and human hypertriglyceridemic (39,40) VLDL uptake can occur through recognition of apo E on the VLDL by LDL receptors. This process was greatly increased by pretreating the VLDL with LPL (37) and it was suggested that the lipase allowed a conformational change in apo E to take place which in turn allowed receptor recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoproteins were separated by centrifugation in 6OTi or 5OTi rotors at 40C in an ultracentrifuge (model L5-50; Beckman Instruments Inc., Fullerton, CA) using standard techniques (5). The lipoproteins were washed once at a heavy density solution.…”
Section: Methodsmentioning
confidence: 99%
“…Reduced VLDL and IDL levels indicate that these particles were rapidly cleared from the plasma, possibly through the receptor-mediated uptake by the liver (29). It has been suggested that after hydrolysis of VLDL triglycerides by LPL, exposure of unreactive apoE, and conformational changes in apoB-100 may enhance binding of VLDL to the LDL receptor (30,31). Merkel et al (32) showed that hepatic expression of LPL increases VLDL mass clearance in LPL-KO mice.…”
Section: Figmentioning
confidence: 99%